Pengaruh Kepemilikan Asing,Keputusan Investasi dan Keputusan Pendanaan terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar diBursa Efek Indonesia Periode 2017-2021) - Tara Diana, Lia; Irnawati, Jeni (Universitas Serang Raya, 2024)
This research aims to determine the influence of Foreign Ownership (X1), Investment Decisions (X2), and Funding Decisions (X3) on Company Value in the Property and Real Estate Sector listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. This research uses associative quantitative methods. The data used in this research is secondary data. The sampling technique in this research used purposive sampling. The data analysis technique used uses the E-Views Serie 12 application. The results of the research show that partially the variables Foreign Ownership (X1), Investment Decisions (X2), and Funding Decisions (X3) together (simultaneously) do not have a significant effect on the value companies in the Property and Real Estate Sector listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. The results of the coefficient of determination test obtained an R-squared value of 0.027779 (2.7%). This means that the independent variable can explain 2.7% of the variation in the dependent variable, while the remaining 97.3% is influenced by other factors that are not modeled. However, researchers hope that companies will continue to maintain company value by paying attention to these three variables to maintain the trust of investors and society in general. Keywords: Foreign Ownership, Investment Decisions, Funding Decisions, CompanyValue.